Morbidities of preterm VLBW neonates and the bacteriological profile of sepsis cases - Hoque, MM; Ahmed, ASMNU; Halder, SK; Khan, MFH; Chowdhury, MAKA (Pulse, 2011)
Background: Preterm very low birth weight babies are at increased risk of perinatal, neonatal and postnatal mortality and morbidity, mainly due to infections and complications of prematurity. Mortality of VLBW neonates is 30 times more than that of normal weight. Outcomes of such infants have been reported extensively from developed countries, but less is known from developing countries like Bangladesh though prematurity is very common. Objective: To determine the morbidities associated with preterm VLBW neonates with particular emphasis on sepsis. Methods: A prospective cohort study was done in Special Care Baby Unit of a tertiary care teaching hospital from July 2009 to December 2009. Preterm VLBW neonates admitted within 7 days of age comprised the cohort for the study. Detailed physical findings and information on pregnancy, delivery and immediate postnatal period were recorded on enrolment. Sepsis workup was done whenever sepsis was suspected clinically. Daily follow-up was given till discharge/death and relevant clinical findings recorded. Data were analyzed using SPSS 12. Results: A total of 738 neonates were admitted during study period, 92 were preterm VLBW and enrolled in the cohort. Fifty-two (56.5%) of the enrolled cases were male and 40 (43.5%) female, male female ratio of 1.3:1. Mean gestational age was 30.8±2.4 weeks and mean birth weight 1,320±133 grams. Eight cases (8.7%) had features of septicaemia on admission and 49 (53.2%) neonates subsequently developed nosocomial infections. Other morbidities were jaundice (34.8%), RDS (8.7%), NEC (4.3%), TTN (3.3%), IVH (2.2%) and PDA (1.1%). Blood culture was positive in 29.8% among 57 suspected sepsis cases; Acinetobacter (41.2%) was the most common organism, followed by Klebsiella pneumoniae (23.5%), Escherichia coli (23.5%) and Pseudomonas sp. (11.8%). Sixty (62.5%) preterm VLBW neonates were improved and discharged, 3 (3.3%) cases were discharged on risk bond and 29 (31.5%) died. Conclusions: Preterm VLBW neonates are at increased risk of morbidity and mortality. Septicemia is the most common and devastating morbidity, most infections are hospital acquired. Therefore strict protocol for asepsis in neonatal units must be adhered to when handling these high risk infants. Key words: Preterm; very low birth weight; septicaemia; morbidity; mortality DOI: http://dx.doi.org/10.3329/pulse.v4i1.6955 Pulse Vol.4 January 2010 p.5-9